The development and validation of a scale to explore staff experience of governance of economic efficiency and quality (GOV-EQ) of health care - Sara Korlén; Anne Richter; Isis Amer-Wåhlin; Peter Lindgren; Ulrica von Thiele Schwarz (BMC, 2018)
Abstract Background In publicly funded health care systems, governance models are developed to push public service providers to use tax payers' money more efficiently and maintain a high quality of service. Although this implies change in staff behaviors, evaluation studies commonly focus on organizational outputs. Unintended consequences for staff have been observed in case studies, but theoretical and methodological development is necessary to enable studies of staff experience in larger populations across various settings. The aim of the study is to develop a self-assessment scale of staff experience of the governance of economic efficiency and quality of health care and to assess its psychometric properties. Methods Factors relevant to staff members' experience of economic efficiency and quality requirements of health care were identified in the literature and through interviews with practitioners, and then compared to a theoretical model of behavior change. Relevant experiences were developed into sub-factors and items. The scale was tested in collaboration with the Department of Rehabilitation Medicine at a university hospital. 93 staff members participated. The scale's psychometric properties were assessed using exploratory factor analysis, analysis of internal consistency and criterion-related validity. Results The analysis revealed an eight factor structure (including sub-factors knowledge and awareness, opportunity to influence, motivation, impact on professional autonomy and organizational alignment), and items showed strong factor loadings and high internal consistency within sub-factors. Sub-factors were interrelated and contributed to the prediction of impact on clinical behavior (criterion). Conclusions The scale clearly distinguishes between various experiences regarding economic efficiency and quality requirements among health care staff, and shows satisfactory psychometric quality. The scale has broad applications for research and practice, as it serves as a tool for capturing staff members' perspectives when evaluating and improving health care governance. The scale could also be useful for understanding the underlying processes of changes in provider performance and for adapting management strategies to engage staff in driving change that contributes to increased economic efficiency and quality, for the benefit of health care systems, patients and staff.